If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X2-6X-72=0
We add all the numbers together, and all the variables
X^2-6X-72=0
a = 1; b = -6; c = -72;
Δ = b2-4ac
Δ = -62-4·1·(-72)
Δ = 324
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:X_{1}=\frac{-b-\sqrt{\Delta}}{2a}X_{2}=\frac{-b+\sqrt{\Delta}}{2a}\sqrt{\Delta}=\sqrt{324}=18X_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-6)-18}{2*1}=\frac{-12}{2} =-6X_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-6)+18}{2*1}=\frac{24}{2} =12
| 1+2(x-4)=9 | | 5(x+2x)=15x+3 | | h/2+8=12 | | 64ss=3 | | 8^x+2=32^2x+4 | | t-217=319 | | 3+-4-5f=f+5+2f | | 6/z^2-2/7z-12=0 | | (-700)x7=1057 | | −1+2x−x=x−8+(−x) | | -7/9m=11/9 | | -10=a/3+3/3 | | 55,000y+2500=62000y+2,000 | | 63x+4x=9 | | -5x-12x+27=-7x-33 | | 0.25X+0.05y=3.90 | | -2.3.4=-1.3w | | 12x+112=1000 | | -10=(a+3)/3 | | 2y+12=6y+2 | | 1/4a=20 | | 12+.5x=15.50 | | 5x+10+2(x-6)=-3x-2 | | 8x2+14x+5=0 | | x+23=910x+23=910 | | n+7=36/6 | | 5d+7-1=-20+7d | | 91=35^x | | 18a+3=3(+) | | n+7=36*6 | | 11x=384 | | 9+5(2v-3)=-2(4v-3)+2v |